(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
This essay attempts to piece together the main trajectories of climate change and global health governance starting with the historical connectedness of the idea of the global. While the Global South and the Global North constitute key concepts in the approach to global governance of key issues such as climate change and health governance, this essay attempts to locate the historical course undertaken by both concepts within the context of colonialism and postcolonialism in the unequal exchanges between these geopolitical entities. The essay argues that the hegemonic relationship between the Global North and South is traceable to colonialism and its epistemic vestiges (manifest, for instance, through state laws and concerns of security) that have an adverse impact on the countries of the Global South where health and climate change governance is concerned. The essay suggests that the majority of the socioeconomic issues currently plaguing the Global South can be attributed to colonialism and imperialism, which were supported in many parts of the world in the 19th and 20th centuries, as well as to the neocolonial and commercial strategies of extractive and exploitative capitalism of the 21st century. The costs of these changes must be considered in the context of a long-standing theme of the Global North’s exploitation of the environment and the people of the Global South, particularly in terms of heritage loss, loss of biodiversity, extreme weather conditions, and even health emergencies like the COVID-19 pandemic. The essay concludes by advocating for a greater inclusion of the Global South in the governance of climate change through hybrid institutional complexes (HICs) in governing the global commons.